Konstruksi Asas Peraturan Daerah Kota Madiun Tentang Perlindungan Dan Pengelolaan Lingkungan Hidup (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2002)
Enforcement of environmental crimes is a serious problem to be tackled. Enforcement will be carried out based on what basic construction is built on environmental regulations. This study will discuss what the basic construction was built on the Madiun City Perda No.19/2011, whether the basic construction built in the Madiun City Regulation No.19/2011 was in accordance with the basic construction in Law No.32/2009 and whether the basic construction Madiun City Regulation No.19/2011 may have implications for the successful achievement of the objectives of the regulation. This research is a normative legal research using secondary data consisting of primary legal materials in the form of laws and regulations and secondary legal materials, namely literature. The results of the study stated that the basic construction that was built in the Regional Regulation of the City of Madiun No.19/2011 was the primum remedium principle. This principle is constructed in the Regional Regulation of the City of Madiun No.19/2011 based on the condition of the City of Madiun which is based on economic, legal and cultural factors. The basic construction that was built is used for law enforcement purposes and makes it easier to achieve the objectives of environmental enforcement in Madiun City which is contained in Article 3 of the Madiun City Regulation No.19/2011. Despite the construction of the primum remedium principle, its application is not normatively applied because it can result in disruption of the economy, law and culture which are the basis for constructing this principle. The persuasive approach is preferred because it provides more benefits for the government, society and development actors. However, the Madiun City Regulation No.19/2011 still applies the principle of primum remedium if the development carried out results in intolerable adverse impacts and as a form of support for the Madiun City Government in carrying out the mandate of the 1945 Constitution Article 28H paragraph (1) to create a good living environment. and healthy. However, the construction of the primum remedium principle cannot be applied in all regions of Indonesia due to different economic, legal and cultural factors in each region. Keywords: development; environment; primum remedium Abstrak Penegakan kejahatan lingkungan hidup menjadi masalah serius untuk ditangani. Penegakan akan dilakukan berdasarkan konstruksi asas apa yang dibangun pada peraturan tentang lingkungan hidup. Penelitian ini akan membahas tentang konstruksi asas apa yang dibangun pada Perda Kota Madiun No.19/2011, apakah konstruksi asas yang dibangun pada Perda Kota Madiun No.19/2011 telah sesuai dengan konstruksi asas pada UU No.32/2009 serta apakah konstruksi asas Perda Kota Madiun No.19/2011 dapat berimplikasi terhadap pencapaian keberhasilan tujuan dari Perda tersebut. Penelitian ini berjenis penelitian hukum normatif dengan menggunakan data sekunder yang terdiri bahan hukum primer yakni berupa peraturan perundang-undang dan bahan hukum sekunder yakni literatur. Hasil penelitian menyatakan bahwa konstruksi asas yang dibangun pada Perda Kota Madiun No.19/2011 adalah asas primum remedium. Asas tersebut dikonstruksikan pada Perda Kota Madiun No.19/2011 berdasarkan kondisi Kota Madiun yang berdasarkan pada faktor ekonomi, hukum dan budaya. Konstruksi asas yang dibangun digunakan untuk tujuan penegakan hukum dan mempermudah mencapai tujuan penegakan lingkungan hidup Kota Madiun yang terdapat pada Pasal 3 Perda Kota Madiun No.19/2011. Meski berkonstruksi asas primum remedium, penerapannya tidak secara normatif diterapkan lantaran dapat berakibat terganggungnya ekonomi, hukum dan budaya yang menjadi dasar untuk mengkonstruksikan asas ini. Pendekatan secara persuasif lebih dipilih lantaran lebih memberikan manfaat bagi pemerintah, masyarakat serta pelaku pembangunan. Meski demikian, Perda Kota Madiun No.19/2011 tetap memberlakukan asas primum remedium jika pembangunan yang dilakukan mengakibatkan dampak buruk yang tidak dapat ditoleransi serta sebagai bentuk dukungan Pemkot Madiun dalam menjalankan amanat UUD 1945 Pasal 28H ayat (1) untuk mewujudkan lingkungan hidup yang baik dan sehat. Meski demikian, konstruksi asas primum remedium tidak dapat diterapkan diseluruh wilayah Indonesi karena faktor ekonomi, hukum dan budaya yang berbeda disetiap wilayah. Kata kunci: lingkungan hidup; pembangunan; primum remedium